KONSEP FLEXIBILITY PADA INTERIOR FASILITAS PENUNJANG PENDIDIKAN DARUL HIKAM INTEGRATED SCHOOL (DHIS) - CARDIAH, TITA; Firmansyah, Rangga; Mulya Raja, Togar; Satria, Muhammad Ridho (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Educational facilities are an important factor in supporting the success and target learning outcomes. Darul Hikam Integrated School (DHIS) - Primary as a school that upholds moral values and develops student creativity, so it requires the support of educational facilities that are in accordance with learning targets, educational programs and of course the school's vision and mission. The purpose of this community service is to help solve space or facility problems in the Darul Hikam Integrated School (DHIS) - Primary for rearrangement that applies the concept of interior space flexibility arrangement to educational facilities. The expected results of this activity are design recommendations that answer problems in educational facilities at Darul Hikam Integrated School (DHIS) – Primary. The method used in this research is problem solving based on existing data and then generating design recommendations. The activity stages are initial data collection, FGD, survey of existing data, data analysis, presentation to partners, design development and the last is presentation or dissemination of activity results. The boundaries/scope of the object of discussion (according to the partner's proposal) are supporting facilities which include hall rooms, lobbies, student waiting rooms, reading corners, lunch drop rooms and circulation pathways. Recommendations for the next stage are library facilities, commonroom and teacher's room.